A novel PNP variant causes lymphopenia, hypouricemia and neurological deficit - Abd Hamid, Intan Juliana; Chen, Bee Chin; Leong, Huey Yin; Yakob, Yusnita; Abd Azize, Nor Azimah; Mohd Khalid, Mohd Khairul Nizam; Ch'ng, Gaik Siew; Keng, Wee Teik; Ngu, Lock Hock (Paediatrica Indonesiana, 2025)
Purine nucleoside phosphorylase (PNP) deficiency is a rare autosomal recessive disorder of the purine metabolism and salvage pathway caused by mutations in the PNP gene. This disorder leads to progressive severe combined immunodeficiency (SCID) and neurological impairment. We report on identification of a 5-year-old Malaysian-Thai girl who presented with T–B–NK–SCID phenotypes and a novel PNP gene mutation. A full analysis of the clinical phenotypes, immunological investigations, and molecular study was performed. She initially presented with spastic diplegia and isolated motor developmental delay. Her blood tests showed lymphopenia and profound hypouricemia, which prompted further investigations for purine deficiency. Urine purine nucleosides, including inosine, guanosine and deoxylated forms, were grossly elevated. The diagnosis was further confirmed by detection of low PNP enzyme activity in hemolysate. Analysis of the PNP gene revealed a novel homozygous mutation c.550C>T, p.(Gln184Ter). Our report highlights the importance of evaluating for SCID in patients presenting with lymphopenia, hypouricemia, and neurological manifestations.